Treatment with milk thistle extract (Silybum marianum), ursodeoxycholic acid, or their combination attenuates cholestatic liver injury in rats: Role of the hepatic stem cells - Alaca, Nuray; Özbeyli, Dilek; Uslu, Serap; Şahin, Hasan Hüseyin; Yiğittürk, Gürkan; Kurtel, Hızır; Öktem, Gülperi; Çağlayan Yeğen, Berrak (Turkish Journal of Gastroenterology, 2017)
Abstract Background/Aims: Cholestasis, which results in hepatic cell death, fibrosis, cirrhosis, and eventually liver failure, is associated with oxidative stress. The aim of this study was to evaluate the effects of milk thistle (MT, Silybum marianum) and ursodeoxycholic acid (UDCA) or their combination on the activation of hepatic stem cells and on the severity of cholestasis liver injury in rats. Materials and Methods: Under anesthesia, bile ducts of female Sprague Dawley rats were ligated (BDL) or had sham operation. BDL rats were administered saline, UDCA (15 mg/kg/d), MT (600 mg/kg/d), or UDCA+MT by gavage for 10 days. On the 11th day, rats were sacrificed and blood and liver samples were obtained. Serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), hepatic malondialdehyde (MDA) levels, and myeloperoxidase (MPO) activity were measured. Hepatic injury, a-smooth muscle actin expression, and stem cell markers c-kit, c-Myc, Oct3/4, and SSEA-1 were histologically determined. Results: Histological scores, serum ALT, and hepatic MDA levels were higher in BDL group than in the sham rats, while all treatments significantly reduced these levels. The reduction in ALT was significantly greater in UCDA+MT-treated group than in other treatment groups. c-Kit, c-Myc, Oct3/4, and SSEA-1 were increased in saline-treated BDL group with respect to sham-operated control group, and these markers were significantly reduced in all treatment groups. Conclusion: In addition to a modulatory effect on the stem cell-induced regenerative response of the liver, UDCA, MT, and their combination demonstrated similar anti-inflammatory and antiproliferative effects on cholestasis-induced hepatic injury. Cite this article as: Alaca N, Özbeyli D, Uslu S, et al. Treatment with milk thistle extract (Silybum marianum), ursodeoxycholic acid, or their combination attenuates cholestatic liver injury in rats: Role of the hepatic stem cells. Turk J Gastroenterol 2017; 28: 476-84.